2010
DOI: 10.1080/07399331003725507
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Mammography Utilization Among Working Muslim Iranian Women

Abstract: Most countries in Middle East have been successful in establishing and furthering basic facilities for screening, diagnosis, and treatment of breast cancer. The rate of compliance with mammography screening, however, remains well below North American and Western European countries. We utilized the Health Belief Model (HBM) to explore factors associated with mammography screening behavior among a sample of 320 Muslim women aged > or = 35. Carrying out this cross-sectional study, we found that screening behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 29 publications
4
28
1
Order By: Relevance
“…In contrast to HBM, perceived susceptibility and perceived severity were not significantly associated with mammography use. This finding is in agreement with findings of previous studies (Farmer et al, 2007;Hatefnia et al, 2010) and is in contrast with some studies.…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast to HBM, perceived susceptibility and perceived severity were not significantly associated with mammography use. This finding is in agreement with findings of previous studies (Farmer et al, 2007;Hatefnia et al, 2010) and is in contrast with some studies.…”
Section: Discussioncontrasting
confidence: 54%
“…Study done in educational institute of Lahore, Pakistan also reported television (14%) and hearsay (17%) as most common sources of information (Khokher, 2011). Similar evidence exists about electronic media and television being the most important sources of information on BC (Montazeri et al, 2010;Ravichandran et al, 2010;Yoo et al, 2012) followed by relatives and friends for less educated women (Hatefnia et al, 2010).…”
Section: Discussionmentioning
confidence: 61%
“…Israeli Arab women were less comfortable with a male examiner than with a female examiner, but the issue was not serious enough to act as a barrier to breast cancer screening. Although deeply Health care providers were found to have inadequate knowledge of breast cancer screening Jordan, Iran Alkhasawneh, 2007;Jaradeen, 2010;Haji-Mahmoodi et al, 2002;Madanat & Merrill, 2002 Adequate knowledge yet only 65% were regularly performing BSE UAE Sreedharan et al, 2010 Professional recommendation was found to be an important facilitator however low percentages of health care providers were found to provide recommendation for breast cancer screening Socio-demographic such as age, education, marital status were not predictors Turkey, UAE Avci & Kurt, 2009;Bener et al, 2001 Informal social support-objection of spouse to breast cancer screening only mentioned by small minority of 2.7% and 8.9% respectively UAE, Qatar Bener et al, 2001& 2009 Fear of losing traditional role as woman as a result of cancer diagnosis as barrier Israel Baron-Epel, 2004;Remmenick, 2006 Fear of losing traditional role as woman not a barrier Israel Soskolne et al, 2007 Fear of losing traditional role as woman was concern but not strong enough to act as barrier Israel Fear of losing traditional role as woman as a facilitator Iran Lamyian et al, 2007 Embarrassment regarding breast cancer screening activities Saudi Arabia, Qatar, UAE, Jordan, Egypt, Israel, Iran Akhtar et al, 2010;Amin et al, 2009;Bener et al, 2009;Bener et al, 2001;Cohen& Azaiza, 2005;Petro-Nustas, 2001b;Seif & Aziz, 2000 Embarrassment only mentioned by 4% Turkey Cam & Gvmvs, 2009 Although embarrassed women expressed this was not enough to act as a barrier Israel, Iran Montazeri, 2003 Fear of gossip regarding breast screening practices Israel Recommendation of breast screening from friend or family Iran, Jordan, Israel Lamyian et al, 2007;Petro-Nustas, 2001b;Soskolne et al , 2007 Religious influences regarding breast cancer screening as a facilitator Israel, Iran Hatefnia et al, 2010 Women expressed religion not to be a barrier for BSE Iran Montazeri et al, 2003 Religious influences regarding breast cancer screening as a ...…”
Section: Barriers To and Facilitators Of Breast Cancer Screeningmentioning
confidence: 99%
“…Self-care as a low priority Egypt, Kuwait, Turkey, Iran, Qatar, UAE Ahmed, 2010;Bener et al, 2001;Bener et al, 2009;Al-Qattan, 2008;Çam & Gϋmϋs, 2009;Hatefnia et al, 2007;Lamyian at al., 2007;Seif & Aziz, 2000 Fear of breast cancer diagnosis as a barrier Qatar, UAE, Yemen, Kuwait, Egypt, Turkey Ahmed, 2010;Al Qattan et al, 2008;Bener et al, 2009;Cam & Gvmvs, 2009;Petro-Nustas, 2001a;Petro-Nustas and Mikhail, 2002;Seif & Aziz, 2000 Fear of breast cancer diagnosis as a barrier or a facilitator Israel Baron-Epel, 2010;Cohen et al, 2005 Fear of pain from mammogram or CBE Israel, UAE, Qatar, Azaiza et al, 2010;Bener et al, 2001;Bener et al, 2009;Soskolne et al, 2007 Fear of pain only mentioned by minority Jordan Petro-Nustas, 2001a Perception of low susceptibility to breast cancer as barrier Israel, Turkey, Iran, Jordan Abbaszadeh et al, 2007;Avci, 2009;Avci & Kurt, 2008;Dundar et al, 2007;Petro-Nustas, 2001a;Petro-Nustas, 2001b;Soskolne et al, 2007 Perception of low susceptibility to breast cancer not found as barrier Iran Hatefnia et al, 2010;Tavafian et al, 2009 Perceived effectiveness of breast cancer screening Israel, Iran, Kuwait, Turkey Abbaszadeh et al, 2007;Avci & Kurt, 2008;BaronEpel, 2010;Hatefnia et al, 2010;Soskolne et al, 2007;Tava...…”
Section: Table 2 (Continue) Barriers and Facilitators Towards Breastmentioning
confidence: 99%
See 1 more Smart Citation